An Introduction to Africana Philosophy - Gordon, Leqis R (Cambridge University Press, 2013)
This book came about through an odd series of circumstances. I was asked to write up a proposal for it while tending to the last rites for the man whose first and last name I share. Those were harrowing times. It was at the end of a year in which, through losing both my parents, I became an orphan. Proposing a text that invokes ancestors as witnesses was something I thought I would not have been able to bear. I found strength and inspiration articulating their contributions and representing this field for Cambridge University Press